The distinct surface of human blood dendritic cells, as observed after an improved isolation method. - Freudenthal, P S (1990)
Prior studies have identified a subset of dendritic cells in human blood, as well as their stimulatory function for T-cell-mediated immune responses. However research has been limited by difficulties in isolation, since dendritic cells make up only 0.1-1% of blood mononuclear cells. We present a protocol that reliably yields preparations that are greater than 80-90% pure. The method relies on the sequential depletion of the major cell types in blood and simultaneously provides T cells, monocytes, and B plus natural killer cells for comparison with dendritic cells. The last step in the procedure is the removal of residual contaminants on the basis of expression of a CD45R epitope. The enrichment of dendritic cells is evident by three criteria, each of which is related to the surface of these antigen-presenting cells. (i) All dendritic cells are motile, constantly forming large lamellipodia or veils. (ii) When analyzed with a large panel of monoclonal antibodies and the FACS, the cells express high levels of all known polymorphic major histocompatibility complex gene products, as well as a distinct combination of receptors and adhesion molecules. Unlike monocytes, for example, dendritic cells lack Fc receptors and the colony-stimulating factor 1 receptor (c-fms) but express much higher levels of ICAM-1 and LFA-3 adhesins. (iii) In functional assays, dendritic cells are at least 100 times more potent than monocytes or lymphocytes in stimulating the primary mixed leukocyte reaction. These properties help make the trace subset of dendritic cells more amenable to further functional and clinical studies.